Sams teach yourself Visual basic 2012 in 24 in hours - Foxall, James D. (Indianapolis, Indiana : Sams Publishing, 2013)
Provides lessons, quizzes, and exercises that cover the basics of Microsoft Visual Basic 2012 to create interfaces and applications.
Keywords: BASIC (COMPUTER PROGRAM LANAGUAGE)